Manfaat Psidium Guajava L. untuk menurunkan kolesterol dalam bentuk teh - Yahya, Azzahra Aulia (Maliki Interdisciplinary Journal, 2024)
Guava (Psidium guajava L.) is a nutrient-rich fruit that is known to have a variety of health benefits, including in managing cholesterol levels. With vitamin C, vitamin A, iron, calcium, and secondary metabolites such as quercetin, anthocyanins, and carotenoids, guava is believed to help lower bad cholesterol (LDL) and increase good cholesterol (HDL). Apart from being consumed directly or in juice form, the fruit can also be processed into tea, providing an alternative consumption for those who don’t like consuming guava in its fresh form. The process of making guava tea involves several steps, namely picking ripe fruits, washing, thin slicing, drying, grinding, filtering, and packaging into an easy-to-brew powder. The bioactive compounds in guava tea work by suppressing LDL while increasing HDL, potentially reducing the risk of cardiovascular diseases such as heart disease and stroke. Regular consumption of this tea within reasonable limits is recommended so that optimal results can be obtained without side effects, as excessive consumption has the potential to cause diarrhea. In addition, the development of guava-based products, such as capsules or extract tablets, may increase the accessibility and acceptability of the health benefits. Further research on the optimal dosage and clinical trials are also needed to ensure the effectiveness and safety of guava tea in the long term. That way, guava tea can be a practical, innovative functional option in an effort to manage cholesterol naturally.